Photosynthetic performance, growth, pigment content, and photoprotective compounds of the mangrove macroalgae Bostrychia calliptera and Bostrychia montagnei (Rhodophyta) under light stress - Borburema, Henrique D. S.; Graiff, Angelika; Marinho-Soriano, Eliane; Karsten, Ulf (Frontiers in Marine Science, 2022)
Increased solar radiation on the Earth’s surface is expected due to global change. Mangrove macroalgae can be negatively affected by increased solar radiation, since some species, such as Bostrychia spp. (Rhodophyta) have been characterized as typical “shade” plants. Thus, we investigated the effects of increasing photon flux densities (PFDs: 170, 267, 443, 638, and 1155 µmol photons m–2 s–1) on the physiological performance of Bostrychia calliptera and Bostrychia montagnei from a tropical mangrove. Several photosynthesis–related parameters indicated that both species decreased their photosynthetic performance under increasing PFDs, with photosynthesis of B. montagnei being more affected than that of B. calliptera. Bostrychia calliptera exhibited highest growth under 638 µmol photons m–2 s–1 while at 1155 µmol photons m–2 s–1 it was inhibited. The highest growth of Bostrychia montagnei was observed under 267 µmol photons m–2 s–1. Higher PFDs led to growth inhibition. The phycobiliprotein and chlorophyll a content of B. montagnei was degraded under increased PFDs. In B. calliptera only chlorophyll a degradation was observed. The mycosporine-like amino acid contents (photoprotective metabolites) of both species were degraded under increasing PFDs, which was more pronounced in B. montagnei. Our results demonstrated that increased solar radiation on estuarine tropical ecosystems will be detrimental to the physiological performance of B. calliptera and B. montagnei. Our results also demonstrated that B. montagnei was more negatively affected by increased light stress than B. calliptera. This can explain its preferential occurrence in more shaded microhabitats compared to B. calliptera. Our data document for the first time light acclimation in the studied macroalgae and the deleterious effects of increased light stress on the genus Bostrychia.